Solanum xanthocarpum fruit extract promotes chondrocyte proliferation in vitro and protects cartilage damage in collagenase induced osteoarthritic rats (article reference number: JEP 114028). (28th June 2021) - Shivnath, Neelam; Siddiqui, Sahabjada; Rawat, Vineeta; Khan, Mohd Sajid; Arshad, Md
Abstract: Ethnopharmacological relevance: Osteoarthritis (OA), a degenerative joint disease, is characterized by cartilage erosion and matrix degradation. Solanum xanthocarpum Schrad. & Wendl. fruits (SXF) and leaves have long been used as folk remedy in the treatment of pain in rheumatism. Aim of the study: This study was aimed to investigate the phytochemical components and protective benefits of SXF on in vitro chondrocytes proliferation, and in vivo suppression of collagenase-induced OA. Materials and methods: Phytochemical components in ethanolic SXF extract were evaluated using gas chromatography-mass spectrometry (GC-MS). Effect of SXF on in vitro cell proliferation of primary chondrocytes was determined by cell proliferation assay and cell cycle analysis by flow cytometry. OA was induced in the right knees of rats through intra-articular injection of collagenase type-II. To evaluate in vivo preventive function of SXF, body weight, blood ALP, histopathological changes in the knee joint, proteoglycan, and collagen content were determined. The mRNA expression of COL-2, MMP-3 and COX-2 genes through qRT-PCR was studied. Antioxidant activities, total phenolics and flavonoid contents of SXF were also examined. Results: GC-MS analysis revealed that SXF constitutes 28 phytochemicals including flavonoids (3-methoxy apigenin, quercetin, luteolin), tannin (quinic acid), terpenes (oleanolic acid, lupeol, psi.psi carotene), phytosterols (campesterol, stigmasterol, β-sitosterol), and ascorbic acid. In vitro studies demonstrated that SXF enhanced the cell proliferation in a dose-dependent manner and has no cytotoxic effect on primary chondrocytes. In vivo study suggests that SXF protects the cartilage destruction induced by collagenase. The histological study revealed that SXF restored the synthesis of collagen and proteoglycan, vital factors for cartilage restoration, and reduced the arthritic score. An up-regulation in COL-2 expression and suppression of MMP-3 and COX-2 were detected by qRT-PCR analysis. Thus, in vivo study suggests the protective effects of SXF on cartilage destruction induced by collagenase. Conclusions: Our results imply that SXF benefits and ameliorates OA by enhancing the chondrocytes proliferation and preventing the articular cartilage damage through the restoration of their structural molecules, arthritic score reduction, suppression of MMP-3 and COX-2 expression level and up regulation of COL-2 genes expression. These results suggest that SXF could be a promising alternative treatment candidate for osteoarthritis. Graphical abstract: Image 1